A study on Filipino stylists in Metro Manila - Bartolome, Pamela Garrido; Escano, Ma. Monica R. (2003.)
The field of fashion is full of career opportunities, one of which is being a stylist. In the Philippines, however, this profession has still yet to receive the recognition it deserves. The researcher realized that there are limited documents regarding the fashion styling profession in the Philippines, thus the researcher decided to study the job responsibilities and duties of the stylists working in Metro Manila through this research. The researcher intended to inquire about the background and training of the selected respondents, determine the skills and characteristics that these respondents deem necessary for their profession, and provide vital information on fashion styling in Metro Manila. Questionnaires were given to seven selected Filipino stylists based in Metro Manila, namely Millet Arzaga, Rexy Bautista, Shahani Gania, Marko Medina, Grace Pagcu, Sydney Rubio-Fortun, and Tara Santos. Along with the study's main objectives, the researcher also utilized the questionnaire to ask the respondents what they know regarding when and how the profession emerged in the country. Books and Internet documents were reviewed for supporting data on the topic of styling, and the researcher made tabulated and made a qualitative analysis on the data gathered through the questionnaires. The researcher discovered that the selected stylists graduated from various courses in college, namely Advertising, Clothing Technology, Communication Arts, Journalism, Mass Communication, Media Production, and Theater Arts. Interest in fashion is generally what led them all to become stylists. The stylist is essentially in charge of creating the look portrayed in the shoot/show, selecting and/or pulling out the clothes, coordinating the details of the shoot/show, ensuring that the merchandise sponsors are given credit, and returning the borrowed clothes to the stores. Various answers were collated from the respondents on what skills and characteristics are needed for their job, but the top answers were: awareness of fashion trends; knowledge, passion and interest for fashion, style, color, arts, etc.; good PR skills or being people oriented; and patience. The respondents had different answers on how they think the job of stylists emerged in the country. Their replies varied from fashion designers being the first stylists, to stylists first practicing in fashion boutiques, theater, television shows, fashion shows, and glossy magazines. However, two of the respondents believe that stylists first practices their expertise in fashion boutiques, while two others think it originated from the fashion show industry. Three respondents perceive the recent flourish of local fashion magazine publications help in promulgating the profession.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Fashion designers -- Philippines